Steel Moment Frames with Ductile Girder Web Opening - Goel, Subhash C.; Stojadinovic, Bozidar; Leelataviwat, Sutat (Engineering Journal, 1997)
An innovative way to improve the performance of moment resisting steel frames is proposed. The upgrading scheme consists of creating rectangular (Vierendeel) openings reinforced with diagonal members in the web of girders near the mid span. Under severe seismic forces, inelastic activity will be limited only to yielding and buckling of diagonal web members and plastic hinging in T-shaped chord members of the openings. Through this scheme, not only is premature fracture of beam-to-column connections is avoided, but widespread and uncontrolled yielding, as observed in many moment frames, is also prevented. This results in improved dynamic response under severe ground motions. An actual existing moment frame building was taken as an example by applying the proposed modification scheme to the moment frames. The responses of the structure to a severe ground motion before and after modification were compared. Finally, a full scale testing of a one story subassemblage was carried out to verify the proposed modification procedure and to verify the results from computer analyses.